Analysis of PT Grab Indonesia’s CSR strategy in facing cuts and capital management during the pandemic - Ivana, Ivana Defrintya Karyadi; Islam, Misbah (Universitas Ahmad Dahlan, 2022)
Currently building a good relationship between the company and the social environment is very important, besides the social environment, building good relationships within the company is also very important. This will affect how a company is run, and how well the company's reputation can be formed. This responsibility is carried out by the Corporate Social Responsibility (CSR) of each company, moreover this is a big challenge for a CSR during a pandemic. Many large companies are experiencing a period of crisis, one of which is PT Grab Indonesia, whose company is engaged in online sales, transportation, and so on. Which ultimately limits PT Grab Indonesia in carrying out its duties, due to the emergence of a pandemic that requires people to stay at home. But on the one hand, this pandemic can also be an opportunity to improve the company's reputation through CSR programs. The purpose of this research is to find out how PT Grab Indonesia's CSR strategy in dealing with cuts and capital management during this pandemic, while still paying attention to employees and the surrounding environment so that no one feels disadvantaged and the reputation remains good. This study uses a descriptive-qualitative research approach with case study analysis method of CSR strategy at PT Grab Indonesia. The result of the study is to find out how PT Grab Indonesia's CSR strategy is in dealing with problems related to cutting and managing capital in order to maintain a good reputation.